Pengaruh Aktivitas Jalan Kaki Terhadap Tekanan Darah Pada Penderita Hipertensi Lansia Di UPT Mojokerto - Fajar Arbi Rajabi Choiri; Pudjijuniarto Pudjijuniarto; Mokhamad Nur Bawono; Ananda Perwira Bakti (Lembaga Pengembangan Kinerja Dosen, 2024)
Hypertension is a non-communicable disease that many people need to pay attention to, especially the elderly, therefore it requires more comprehensive and integrated treatment over a long period of time. Uncontrolled hypertension results in a 7 times chance of suffering a stroke, a 6 times chance of suffering from coronary heart disease and a 3 times chance of suffering a heart attack. Based on this description, researchers are interested in conducting research on the effect of walking activity on blood pressure in elderly hypertensive sufferers at UPT Mojokerto. The aim of this study was to determine the effect of walking activity on blood pressure in elderly hypertensive sufferers at UPT Mojokerto. This type of research method is experimental. With a Pre-Experimental research design, and using a One Group Pretest-Posttest research design. From a population of 46 elderly people at UPT Pesanggrahan Mojokerto, a sample of 10 elderly people was taken. Determining the number of samples using purposive sampling. The instrument used is a sphygmomanometer. Implement a 30 minute walking activity exercise program for 2 weeks at a frequency of 3 times per week. The data analysis techniques used are descriptive tests, normality tests using Shapiro-Wilk and hypothesis testing using paired tests in the SPSS statistical version 23 application. The results of the descriptive test research showed that the average difference between pretest and posttest diastolic blood pressure was (4.00 mmHg) and the average difference between pretest and posttest systolic blood pressure (6.00 mmHg). And from the hypothesis test, the t-count significance value = 0.004 with a significance level of α = 0.05. Because the p-value is <0.05, there is an influence of walking activity on reducing the blood pressure of hypertension in the elderly at UPT Pesanggrahan Mojokerto.